Vessel-centered laparoscopic total mesorectal excision via medial approach - Li, Xinxiang; Liang, Lei; Shi, Debing; Ma, Yanlei; Li, Qinguo (Translational Cancer Research; Vol 7, No 3 (June 27, 2018): Translational Cancer Research, 2018)
Total mesorectal excision (TME) is currently the standard treatment for rectal cancer. This procedure provides significant oncological benefits by reducing local recurrence and increasing 5-year survival. Laparoscopic surgery for colorectal cancer has been steadily developing since its introduction in 1990, and laparoscopic TME (lap TME) is an ideal minimally invasive surgical technique for rectal cancer. Compared with laparotomy, laparoscopic surgery has similar safety, completeness of resection, and prognosis (1,2).